2022
DOI: 10.1111/jocd.15276
|View full text |Cite
|
Sign up to set email alerts
|

Combination radiofrequency microneedling and carbon dioxide laser for acne scarring: A systematic review and retrospective case series across two centers

Abstract: Acne scars have been found to negatively impact quality of life with associated adverse psychosocial impact. [1][2][3] Treatment of acne scarring is a therapeutic challenge with a number of available treatment options including topical skincare, chemical peels, dermabrasion, microneedling, dermal filler injections, platelet-rich-plasma injections, lasers, other energy-based devices, and surgery. [4][5][6] These options carry varying degrees of effectiveness and different side effect profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several studies have assessed the safety and effectiveness of the combination of FMR and AFL for treating acne scarring, all of which showed a significant reduction in acne scar severity scores with acceptable safety profiles. 2 10 12 13 Meanwhile, several studies have reported improvements in inflammatory acne assessed by acne severity scoring or lesion counts with FMR treatment. 8 11 In our study, the FMR+AFL treatment demonstrated superior efficacy compared to AFL monotherapy in patients with both inflammatory acne and post-acne scars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have assessed the safety and effectiveness of the combination of FMR and AFL for treating acne scarring, all of which showed a significant reduction in acne scar severity scores with acceptable safety profiles. 2 10 12 13 Meanwhile, several studies have reported improvements in inflammatory acne assessed by acne severity scoring or lesion counts with FMR treatment. 8 11 In our study, the FMR+AFL treatment demonstrated superior efficacy compared to AFL monotherapy in patients with both inflammatory acne and post-acne scars.…”
Section: Discussionmentioning
confidence: 99%
“…First, RF microneedling induces mechanical disruption of dermal fibrotic strands and collagen remodeling; subsequently, AFL irradiation causes epidermal resurfacing by controlled tissue vaporization on the demarcated scar margins. 2 12 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation